KRAS-specific antibody binds to KRAS protein inside colorectal adenocarcinoma cells and inhibits its localization to the plasma membrane - Lam, Kuen Kuen; Low, Yee Syuen; Lo, Michelle; Wong, Michelle; Leong Tang, Choong; Tan, Emile; Chok, Aik Yong; Seow-En, Isaac; Wong, Siew Heng; Cheah, Peh Yean (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is the third highest incidence cancer and a leading cause of cancer mortality worldwide. To date, chemotherapeutic treatment of advanced CRC that has metastasized has a dismayed success rate of less than 30%. Further, most (80%) sporadic CRCs are microsatellite-stable and are refractory to immune checkpoint blockade therapy. KRAS is a gatekeeper gene in colorectal tumorigenesis. Nevertheless, KRAS is ‘undruggable’ due to its structure. Thus, focus has been diverted to develop small molecule inhibitors for its downstream effector such as ERK/MAPK. Despite intense research efforts for the past few decades, no small molecule inhibitor has been in clinical use for CRC. Antibody targeting KRAS itself is an attractive alternative. We developed a transient ex vivo patient-derived matched mucosa-tumor primary culture to assess whether anti-KRAS antibody can be internalized to bind and inactivate KRAS. We showed that anti-KRAS antibody can enter live mucosa-tumor cells and specifically aggregate KRAS in the cytoplasm, thus hindering its translocation to the inner plasma membrane. The mis-localization of KRAS reduces KRAS dwelling time at the site where it tethers to activate downstream effectors. We previously showed that expression of SOX9 was KRAS-mutation-dependent and possibly a better effector than ERK in CRC. Herein, we showed that anti-KRAS antibody treated tumor cells have less intense SOX9 cytoplasmic and nuclear staining compared to untreated cells. Our results demonstrated that internalized anti-KRAS antibody inhibits KRAS function in tumor. With an efficient intracellular antibody delivery system, this can be further developed as combinatorial therapeutics for CRC and other KRAS-driven cancers.